2016
DOI: 10.3347/kjp.2016.54.5.625
|View full text |Cite
|
Sign up to set email alerts
|

A First Case of Human Trichuriasis from a Roman Lead Coffin in France

Abstract: A paleoparasitological study was carried out on 2 lead coffins recovered from the Roman site of Jaunay-Clan (near Poitiers, France). For the first time, this particular type of burial gave positive parasitological results, and eggs of the whipworm Trichuris trichiura were identified in 1 individual. In the present case, thanatomorphose associated with funerary practices may explain the scarcity of the recovered eggs. However, human whipworm has now been observed in 9 individuals dated to the Roman period. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Whipworm and roundworm have been found together at Roman period sites in Austria, Belgium, Britain, France, Germany, Greece, Israel, and the Netherlands (Anastasiou et al, 2017;Aspöck et al, 1999;Bouchet et al, 2001;Boyer, 1999;Gourevitch et al, 2011;Jansen and Over, 1962;Jones, 1985;Jones, 1987;Jones and Hutchison, 1991;Knights et al, 1983;Kuijper and Turner, 1992;Pike, 1968;Rouffignac, 1985;Rousset et al, 1996;Wilson and Rackham, 1976;Zias et al, 2006). However, there are also four sites where roundworm has been found without whipworm (Dittmar et al, 2002;Harter, 2003;Aspöck et al, 2011;Williams et al, 2017), and six sites where whipworm has been found without roundworm (Witenberg, 1961;de Moulins, 1990;Carrott et al, 1995;van Geel et al, 2003;Heirbaut et al, 2011;Dufour et al, 2016). The sample type does not appear to affect the preservation of these two parasites, as both species occur in latrine sediment, mummified remains, pelvic soil, and occupation layer sediment.…”
Section: Discussionmentioning
confidence: 99%
“…Whipworm and roundworm have been found together at Roman period sites in Austria, Belgium, Britain, France, Germany, Greece, Israel, and the Netherlands (Anastasiou et al, 2017;Aspöck et al, 1999;Bouchet et al, 2001;Boyer, 1999;Gourevitch et al, 2011;Jansen and Over, 1962;Jones, 1985;Jones, 1987;Jones and Hutchison, 1991;Knights et al, 1983;Kuijper and Turner, 1992;Pike, 1968;Rouffignac, 1985;Rousset et al, 1996;Wilson and Rackham, 1976;Zias et al, 2006). However, there are also four sites where roundworm has been found without whipworm (Dittmar et al, 2002;Harter, 2003;Aspöck et al, 2011;Williams et al, 2017), and six sites where whipworm has been found without roundworm (Witenberg, 1961;de Moulins, 1990;Carrott et al, 1995;van Geel et al, 2003;Heirbaut et al, 2011;Dufour et al, 2016). The sample type does not appear to affect the preservation of these two parasites, as both species occur in latrine sediment, mummified remains, pelvic soil, and occupation layer sediment.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 2 stone sarcophagi have been analyzed in paleoparasitology up to now, both from the same Roman site of Jaunay-Clan, in France. In these burials, one of the 2 individuals tested positive to the human whipworm Trichuris trichiura [8].…”
mentioning
confidence: 99%